KONSEP PENDIDIKAN ANAK DALAM ISLAM PERSPEKTIF IBNU QAYYIM AL-JAUZIYYAH - Mainuddin, Mainuddin; Fitri , Nur (Al-Lubab : Jurnal Penelitian Pendidikan dan Keagamaan Islam, 2021)
Children are the next generation of the nation, so the good and bad of a child in the future is determined by the child in the present. They will be able to become the hijab of hell fire when educated with the majesty and beauty of Islam. Good education starts from the family, because from them later quality generations will change the face of the world. For this reason, Islam has provided guidance to parents to pay attention to the education of their children. Given the aim of tarbiyah is to maintain the sanctity of human nature and protect it so that it does not fall into deviation and manifest in the child a servitude to Allah Ta'ala.This study intends to answer the problem of how the method of children's education in the perspective of Ibn Qayyim Al-Jauziyah. The results of the study indicate that several educational methods described by Ibn Qayyim Al-Jauziyah are (1) Be fair to children in giving and forbidding, (2) Smearing the baby's tongue with honey and salt to facilitate speech, (3) always being guarded from things - surprising things, (4) Pay attention to and take care of children, (5) Teach children to do good, and (6) pay attention to children's talents. Keywords: Child Education, Ibnu Qoyyim Al-Jauziyyah